Interconnectedness in the CDS Market. Issue 4 (1st July 2016) - Getmansky, Mila; Girardi, Giulio; Lewis, Craig
Abstract : Concentrated risks in the market for credit default swaps (CDSs) are widely considered to have contributed significantly to the 2007–08 financial crisis. We examine the structure of the CDS market using a network-based approach that allows us to capture the interconnectedness between dealers and nondealers of CDS contracts. We find a high degree of interconnectivity among major market participants. Our work helps assess the stability of the CDS market and the potential contagion among market participants. Our findings are of practical importance because even after central clearing becomes mandatory, counterparty risk will remain a relevant systemic consideration owing to the long-term nature of CDS contracts. Abstract : Editor's note : This article was reviewed and accepted by Robert Litterman, executive editor at the time the article was submitted. Authors' note : All three authors worked at the US Securities and Exchange Commission when they wrote this article. As a matter of policy, the SEC disclaims responsibility for any private publication or statement of any of its employees. The views expressed herein are those of the authors and do not necessarily reflect the views of the SEC or of the authors' colleagues on the staff of the SEC.